1978
DOI: 10.1073/pnas.75.12.6073
|View full text |Cite
|
Sign up to set email alerts
|

DNAs of simian virus 40 and polyoma direct the synthesis of viral tumor antigens and capsid proteins in Xenopus oocytes.

Abstract: Purified simian virus 40 and polyoma DNAs injected into nuclei of Xenopus Nuclei from various eukaryotic cells injected into frog oocyte nuclei (germinal vesicles) continue to direct synthesis of origin-specific proteins (1). In addition, genes that were not expressed in the donor cell may be activated after injection (2). Purified viral, phage, or plasmid DNAs injected into the nucleus of Xenopus oocytes serve as templates for the transcription of specific RNA sequences (3). The synthesis of 5S RNA (4) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

1980
1980
1994
1994

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(22 citation statements)
references
References 37 publications
0
22
0
Order By: Relevance
“…Previously, there have been conflicting reports on enhancer activity in Xenopus oocytes. Simian virus 40 (SV40) genes are expressed when SV40 DMA is injected into the oocyte nucleus (de Robertis and Mertz, 1977;Rungger and Türler, 1987). Specifically, the SV40 enhancer in its natural viral context was reported to activate the early promoter (Spinelli and Ciliberto, 1985), while it was inactive in our globin reporter gene constructions (our unpublished data).…”
Section: Introductionmentioning
confidence: 99%
“…Previously, there have been conflicting reports on enhancer activity in Xenopus oocytes. Simian virus 40 (SV40) genes are expressed when SV40 DMA is injected into the oocyte nucleus (de Robertis and Mertz, 1977;Rungger and Türler, 1987). Specifically, the SV40 enhancer in its natural viral context was reported to activate the early promoter (Spinelli and Ciliberto, 1985), while it was inactive in our globin reporter gene constructions (our unpublished data).…”
Section: Introductionmentioning
confidence: 99%
“…The observation that X. laevis oocytes injected with heterologous molecules are capable of performing the myriad of events from chromatin assembly (27,47) and transcription (7,8,11,15,20,25,26,28,35,40) to protein secretion (24) suggests that they might be useful for studies on the regulation of gene expression. Indeed, they have served as an efficient test system to identify DNA sequences involved in the initiation of transcription (25).…”
Section: Discussionmentioning
confidence: 99%
“…The fusion was such that the E3 control region is adjacent to the CAT coding sequences and CAT expression is dependent upon transcription initiated from this region. Flanking the 3' end of the CAT sequences are the simian virus 40 Plasmids pJOLC3E and pJN20E are derivatives of pJOLC3 and pJN20, respectively, that contain an additional insert from the SV40 genome which encodes the 72-bp repeat, enhancer sequences (3,19,30). The insert is the HindIlI C fragment from the SV40 genome and was inserted into the unique Hindlll sites of the Ela-containing plasmids.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…With these studies in mind we initiated studies on the cloning and characterization of the origins in Xenopus laevts (the African clawed frog), which has been widely used to study the expression (transcription and translation) of foreign genes in oocytes (8)(9)(10)(11)(12). It also has been shown that unfertilized X. laevt eggs have the ability to support DNA replication from injected exogenous DNA (13)(14)(15).…”
mentioning
confidence: 99%